Inflasi, Harga Saham, dan Kinerja Keuangan: Analisis Komparatif Perusahaan Manufaktur BEI pada Masa Pandemi dan Pasca Pandemi COVID-19 - Paulina Kinanti Eka Praningtyas; Risma Nurhapsari; Erlinda Sholihah; Aftuqa Sholikatur Rohmania (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The purpose of this study is to examine how inflation and stock prices influence the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. During the pandemic, the manufacturing sector faced considerable economic pressure due to mobility restrictions and supply chain disruptions. In the post-pandemic period, the sector continued to encounter challenges, particularly rising inflation and shifts in market conditions. This research adopts a quantitative approach. The data used are secondary data obtained from official macroeconomic publications and companies’ annual financial reports. In this study, inflation and stock prices serve as the independent variables, while financial performance is measured using Return on Assets (ROA). The data are analyzed using multiple linear regression to assess both partial and simultaneous effects. The findings indicate that inflation does not have a significant effect on ROA, whereas stock prices have a positive and significant impact on the financial performance of manufacturing firms. Simultaneously, inflation and stock prices together influence ROA, although the explanatory power of the model remains moderate. These results suggest that during periods of economic disruption and recovery, market indicators reflected in stock prices play a more prominent role in shaping corporate financial performance than macroeconomic inflationary pressures.